To Know Them is to Love Them - Eugene Hunn (Ethnobiology Letters, 2014)
I connect the theoretical emphasis that motivated the cognitive ethnobiology of the 1960s and early 1970s with the contemporary emphasis on promoting ethnobiology as contributing to biodiversity conservation. I use the words of a popular song to highlight the necessary, if problematic, links between knowing nature – the focus of cognitive ethnobiology, loving nature, and acting to conserve nature. I argue that a highly elaborated knowledge of the living things in one's local environment is characteristic of Indigenous and other deeply rooted communities, which are dependent on sustainable harvests of local natural resources. Furthermore, this extensive knowledge goes hand in hand with a deep emotional engagement with those species (“love”), which is in turn powerful motivation to treat those species with respect, absent dominance of profit motives. I suggest in conclusion that ethnobiology may best contribute to biodiversity conservation by documenting the detailed knowledge of and cultural appreciation for biodiversity evident in such rooted communities – an effort that has defined the ethnobiological project for over the past half century. The wider community of activists dedicated to biodiversity conservation may thus better know and thus appreciate – respect, if not “love” – those who live with and depend for their livelihood on this biodiversity.